Recyclable rhodium-catalyzed C–H activation/[4 + 2] annulation with unconventional regioselectivity at ambient temperature: experimental development and mechanistic insight. Issue 18 (30th August 2022) - Meng, Haifang; Xu, Huiying; Zhou, Zhi; Tang, Zhenhao; Li, Yidi; Zhou, Yu; Yi, Wei; Wu, Xiaowei
Abstract : A robust and convenient rhodium-catalyzed unconventionally regioselective C–H activation/[4 + 2] annulation for the synthesis of isoquinolones which are prevalent in natural products and pharmaceuticals was developed. Abstract : C–H activation provides a straightforward approach to construct new chemical bonds and privileged heterocycles. However, due to common deficiencies, C–H activation still faces a great challenge towards sustainability and applications. Described herein is a robust and convenient rhodium-catalyzed regioselective C–H activation/[4 + 2] annulation for the synthesis of isoquinolones with salient features including a recyclable catalytic reaction system, unique regioselectivity, gram-scale synthesis with low catalyst loading ( e.g., 0.5 mol%), ethanol as the green solvent, air and water compatibility, and simple purification processes. The roles of the hydroxy group and the pivaloyl part in both substrates, the additional pivotal function of propargyl alcohol partners, and the origin of the unique chemoselectivity are clarified based on integrated experimental and DFT studies. Additionally, a propargyl alcohol-connected distinctive hydrogen bonding network with the hydroxy group and the pivaloyl part is also rationally deduced for conferring the observed reverse regioselectivity by subsequent IGMH analysis.